The Elateridae (Coleoptera) of the Maritime Provinces of Canada: faunal composition, new records, and taxonomic changes - Majka, Christopher G.; Johnson, Paul J. (Zootaxa, 2008)
The Elateridae in the Maritime Provinces of Canada is surveyed. One hundred and twenty-five species have been recorded, 110 in Nova Scotia, 98 in New Brunswick, and 48 on Prince Edward Island. Of these, 117 are Nearctic, four are Holarctic, and four are introduced Palaearctic species. Twenty-four species are newly recorded in Nova Scotia, 13 in New Brunswick, and 27 on Prince Edward Island, for a total of 64 new provincial records. Fourteen species including Dalopius gentilis Brown, Dalopius pennsylvanicus Brown, Ampedus areolatus (Say), Ampedus laesus (LeConte), Ampedus nigricollis (Herbst), two undescribed species of Ampedus, Aeolus mellillus (Say), Athous posticus (Melsheimer), Athous productus (Randall), Athous scapularis (Say), Hypoganus sulcicollis (Say), Sylvanelater mendax (LeConte), and Negastrius exiguus (Randall) are newly recorded in the Maritime Provinces as a whole, and one species, Dalopius pennsylvanicus, is newly recorded in Canada. Two species are removed from the faunal list of New Brunswick and two from the faunal list of Nova Scotia. Taxonomic changes proposed are: Anostirus vernalis (Hentz), new combination; Anostirus bipunctatus (Brown), new combination; Anostirus exclamationis (Fall), new combination; Beckerus new genus; Beckerus appressus (Randall), new combination; Beckerus barri (Lane), new combination; Corymbitodes dorothyae (Knull), new combina-tion; Corymbitodes elongaticollis (Hamilton), new combination; Corymbitodes moerens (LeConte), new combination; Corymbitodes pygmaeus (Van Dyke), new combination; Corymbitodes tarsalis (Melsheimer), new combination; Corymbitodes xanthomus (Horn), new combination; Metanomus blaisdelli (Van Dyke), new combination; Metanomus insidiosus (LeConte), new combination; Metanomus shastensis (Van Dyke), new combination; Nitidolimonius new genus; Nitidolimonius appalachius (Van Dyke), new combination; Nitidolimonius breweri (Horn), new combination; Nitidolimonius resplendens (Eschscholtz), new combination; Nitidolimonius weidtii (Angell), new combination; Paractenicera new genus; Paractenicera exilis (Notman), new combination; Paractenicera fulvipes (Bland), new combi- nation; Pseudanostirus hamatus (Say), new combination; Sylvanelater, new genus; Sylvanelater cylindriformis (Herbst), new combination, Sylvanelater furtivus (LeConte), new combination; Sylvanelater limoniiformis (Horn), new combination; Sylvanelater mendax (LeConte), new combination; and Elater viridis Say is regarded as a nomen dubium.